How Is Spatial Planning Adapting to Climate Change? A Textual Analysis Based on the Territorial and Spatial Plans of 368 Chinese Cities - Kebin Zhou; Shifu Wang; Yucheng Feng (Land, 2023)
Spatial planning is broadly acknowledged for its pivotal role in local climate change adaptation. Nevertheless, variations persist among countries in their perceptions and practices concerning the effectiveness and feasibility of utilizing spatial planning for climate change adaptation. Chinese cities confront the challenges of global warming, rapid urbanization, and intensified extreme weather events. Climate change adaptation agreements, frameworks, and policies have predominantly emphasized the national scale, often overlooking local adaptation efforts. However, the ongoing reform and restructuring of China’s territorial and spatial planning system encompasses the categorization, hierarchical management, control of comprehensive national land resource development, and conservation. This process is gradually establishing spatial planning strategies that synergize with the impacts of climate change, thereby offering an opportunity to integrate climate change adaptation objectives into spatial planning. This endeavor is supported by a series of regulatory standards and guidelines to ensure its effective implementation. The study scrutinizes the public draft of territorial and spatial master plans for 368 Chinese cities to assess the integration of climate change concerns at the local level and to identify disparities among cities. Employing the Awareness, Analysis, and Action Framework (3A Framework), which draws from prior scholarship and integrates relevant existing research, we identified and assessed 30 criteria for recognizing and appraising climate change adaptation strategies in territorial and spatial planning. The study’s findings indicate that: (1) The role of territorial and spatial planning in integrating climate change issues at the city level requires enhancement, as reflected in the generally low “awareness” of climate change concerns, limited “analytical capacity” regarding climate change, and a certain foundation for “action response” to climate change adaptation; (2) Large cities, characterized by robust economies and population concentrations, generally outperform small and medium-sized cities. They exhibit a superior ability to delineate quantifiable climate adaptation indicators and measures. In conclusion, the study provides prospective recommendations concerning technical approaches, spatial governance, mechanisms, and actions to more effectively incorporate climate change adaptation objectives into local-level territorial and spatial planning.